Multi-Task Portable Iot-Based Remote Control Vehicle for Area Monitoring Using Arduino Uno R3 With Alarm, Night Vision, and Heat Sensor: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In recent years, the development of portable and Internet of Things (IoT) technologies hasrevolutionized the way we monitor and control various systems remotely. It describes physicalitems that have sensors and actuators built in that may connect to computing systems acrosswired or wireless networks to monitor or even control the physical environment. The multi-taskportable IoT-based remote control vehicle for area monitoring using Arduino Uno R3 withalarm, night vision, and heat sensors is an innovation of these electronics mechanisms thatintegrates several sensors and Arduino Uno R3 as the microcontroller. The Prototypecontains a night vision camera for low-light conditions, an alarm that is intended to alert aspecific person or group of individuals and a heat sensor that provides an efficient yetinexpensive way to measure temperature and humidity. The proposed system can beremotely controlled through a mobile app-based user interface, allowing users to monitor anarea in real time and detect potential security threats.According to the strategy that was described, this chapter gives specific findings. It providesinformation on the prototype's hardware and software as well as the results of tests conductedon the multi-task portable IoT-based remote control vehicle for area monitoring using ArduinoUno R3 with alarm, night vision, and heat sensors.After testing, researchers found that the sensor components used were compatible withArduino Uno R3 to read data and send information to NodeMCU ESP8266 using serialcommunication between the two of them. The NodeMCU and ESP32 Camera can connect tothe internet, display some information on the Blynk Application, and control the vehicle.
Keywords: Computer Science; Engineering